An exploratory investigation of teaching innovations and learning factors in a lean manufacturing systems engineering course. (2nd November 2017) - Choomlucksana, Juthamas; Doolen, Toni L.
ABSTRACT: The use of collaborative activities and simulation sessions in engineering education has been explored previously. However, few studies have investigated the relationship of these types of teaching innovations with other learner characteristics, such as self-efficacy and background knowledge. This study explored the effects of collaborative activities and simulation sessions on learning and the relationships between self-efficacy beliefs, background knowledge, and learning. Data were collected from two different terms in an upper division engineering course entitled Lean Manufacturing Systems Engineering. Findings indicated that the impact of collaborative activities and simulation sessions appears to be different, depending on the concepts being taught. Simulation sessions were found to have a significant effect on self-efficacy beliefs, and background knowledge had a mixed effect on learning. Overall the results of this study highlight the complex set of relationships between classroom innovations, learner characteristics, and learning.